2020
DOI: 10.1002/ctm2.39
|View full text |Cite
|
Sign up to set email alerts
|

T‐cell activation and immune memory enhancement induced by irreversible electroporation in pancreatic cancer

Abstract: Background Irreversible electroporation is shown to induce immune changes in pancreatic cancer while the histology evidences are still lacking. The aim of this study is to show the immune changes in histology and explore whether irreversible electroporation (IRE) can induce immunogenic cell death (ICD) of tumor cells and activate specific immune responses. Methods Subcutaneous and orthotopic pancreatic cancer models were established and used to evaluate the effect of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 44 publications
2
62
0
1
Order By: Relevance
“…Several existing studies indicated that IRE induces immune responses that provide local or systemic protection against tumor recurrence. 18,23,31 This effect has been accompanied by an increase in CD4 + and CD8 + T cells, not only in TME but also in peripheral blood, which could be regarded as T cell activation. 22,23 The activation of the function or increase in the number of T cells can be partly dependent on the increase of co-stimulatory signals, indicating the activation of prime immune responses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several existing studies indicated that IRE induces immune responses that provide local or systemic protection against tumor recurrence. 18,23,31 This effect has been accompanied by an increase in CD4 + and CD8 + T cells, not only in TME but also in peripheral blood, which could be regarded as T cell activation. 22,23 The activation of the function or increase in the number of T cells can be partly dependent on the increase of co-stimulatory signals, indicating the activation of prime immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…The electroporation of percutaneous or orthotopic tumor in vivo and was performed according to the methods reported in our previous study. 18 For the electroporation experiments of cells in vitro, tumor cells were trypsinized, resuspended in phosphate-buffered saline (PBS) at 2 × 10 6 cells mL −1 , and added to an electroporation cuvette (1652088; BTX, Holliston, Massachusetts, 01746, USA) embedded with two aluminum plate electrodes 4 mm apart. The cell suspension was in direct contact with the plate electrodes, and subjected to electroporation at room temperature with the following parameters: voltage: 200-600 V; pulse duration: 100 µs; pulse repetition frequency: 1 Hz; number of repetition pulses: 8, 16, and 24.…”
Section: Electroporationmentioning
confidence: 99%
See 1 more Smart Citation
“…This process preserves adjacent structures by contributing to DC activation and maturation as well as immune cell infiltration. An increase in T-cell levels after IRE has been reported in several mouse models [ 114 , 115 ]. Recently, the combination of IRE and anti-PD1 treatment has been shown to promote selective tumor infiltration by CD8 + T cells, and to significantly suppress tumor growth and prolong survival of immunocompetent mice bearing pancreatic cancer and melanoma [ 116 ].…”
Section: Clinical Trials Exploiting the Efficacy Of Agents And Thementioning
confidence: 99%
“…IRE succeeded in boosting already existing T cell response and in its induction de novo [ 94 ]. Among lymphocytes, CD8+ and CD4+ T-cells are the main agents in anti-tumor response triggered by IRE [ 98 , 99 ]. Few experiments evaluated the possibility of performing IRE together with immunotherapy.…”
Section: Irementioning
confidence: 99%